Use of seatbelts by vehicle occupants in University College Hospital, (U.C.H) Ibadan, Nigeria (2005)
Road traffic accidents are a major cause of death and disability worldwide. A number of mecha nisms have been put in place to reduce the ensu ing injuries, one of which is the use of seatbelts. This observational study was carried out to de termine seatbelt use by vehicle occupants in Uni versity College Hospital (U.C.H). Trained re search assistants observed drivers and other ve hicle occupants as they drove into the only fuel station within the hospital premises between 8.30a.m and 6.00 p.m. over a six-day period. Data on vehicle occupant characteristics, pres ence and use of installed seat belts was docu mented using a modified version of the FIA foun dation sample seatbelt wearing observation form. A total of 570 occupants in 402 vehicles were observed. There were 402 drivers and 117 and 50 front and rear seat occupants respectively. The only child observed was unrestrained and seated on an adults lap in the front. Seat belt use by the drivers, front and rear seat passengers were 76 (18.9%), 16 (13.7%) and 2 (4%) respectively. A higher proportion 29 (29.9%) of all female drivers compared with male drivers 47 (15.4%) were restrained (X2 = 9.152, p = 0.02). Overall seat belt use observed was 16.5% and driver use was only 18.9% in spite of the existence of a law mandating use of seatbelt by drivers. Better enforcement of the current law is necessary and it should be extended to cover other vehicle occupants. The hospital environment presents a good opportunity to edu cate the public on the importance of seatbelt use utilizing various health education methods.